2013
DOI: 10.1590/s1676-06032013000400003
|View full text |Cite
|
Sign up to set email alerts
|

Larval trematodes in freshwater gastropods from Mato Grosso, Brazil: diversity and host-parasites relationships

Abstract: trematodes in freshwater gastropods from Mato Grosso, Brazil: diversity and host-parasites relationships. Biota Neotrop. 13(4): http://www.biotaneotropica.org.br/v13n4/en/abstract?article+bn00613042013Abstract: A survey for freshwater gastropods carrying trematodes parasites was conducted in Manso Dam and the surrounding areas frequented by tourist, focusing particularly on the Pantanal region. Infected snails were recovered from twelve of the eighteen investigated municipalities and forty-one cercaria-snail p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
2
0
1
Order By: Relevance
“…Among ampullariids, only P. paludosa has been definitively demonstrated as a vector, and only of cercarial dermatitis, in Florida (Hanning & Leedom, 1978). In Brazil, although there is no record of cercarial dermatitis associated with species of Pomacea, schistosomatid cercariae have been detected in P. lineata and P. maculata by Mattos et al (2013) and in P. figulina by Thiengo (unpublished).…”
Section: Cercarial Dermatitismentioning
confidence: 99%
“…Among ampullariids, only P. paludosa has been definitively demonstrated as a vector, and only of cercarial dermatitis, in Florida (Hanning & Leedom, 1978). In Brazil, although there is no record of cercarial dermatitis associated with species of Pomacea, schistosomatid cercariae have been detected in P. lineata and P. maculata by Mattos et al (2013) and in P. figulina by Thiengo (unpublished).…”
Section: Cercarial Dermatitismentioning
confidence: 99%
“…From the four places analyzed, only Cáceres was reported in Paraense's study 32 , who found only three species there. Mollusks make possible the biological cycles of several trematodes involving birds, amphibians, fish, reptiles, and mammals, many of which are still unknown, as reported by Mattos et al 33 , who recorded seven cercaria types in the study area.…”
Section: /10mentioning
confidence: 61%
“…Em Pernambuco, Thiengoe outros autores(2010) registraram a presença de larvas de Angyostrongiluscantonensis, parasita causador da angiostrongilíase no homem, em Pomacealineata oriundo de ambiente natural, denotando a potencialidade deste molusco comovetor desta enfermidade. Este gênero também atua como hospedeiros de diferentes tipos de trematódeos (MATTOS et al, 2013).…”
Section: Resultsunclassified